Mkhaʼ ʼgro sñan rgyud kyi Yum bkaʼ rgyas paʼi dkyil chog byin rlabs myur ʼbebs źes bya ba bźugs so - Padma-dkar-po, ʼBrug-chen IV, 1527-1592 (s.n., 1975)
Liturgical text explaining the method for the performance and initiation into the mandala of Vajravarahi according to the traditions of the Drukpa Kargyudpa sect.